1996
DOI: 10.1007/s002560050135
|View full text |Cite
|
Sign up to set email alerts
|

Hill-Sachs lesion: sonographic detection

Abstract: In the detection of Hill-Sachs lesion US showed a sensitivity of 91% (21 of 23), a specificity of 95% (60 of 63) and an accuracy of 94% (81 of 86) when compared with CTA, and a sensitivity of 94% (18 of 19), specificity of 91% (61 of 67) and accuracy of 91% (79 of 86) when compared with arthroscopy. In only 2% (2 of 86) of patients was there reduced visualization because of restriction of movement. Hill-Sachs lesion and its relationship to the humeral head can be reliably diagnosed with US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Identification of large Hill-Sachs lesions is important because it may indicate a predisposition for recurrent luxation. Our results, 91 % (71 out of 80 shoulders), are similar to other previous reports, such as 88 % (54 out of 61 shoulders) [3] and 94 % (81 out of 86 shoulders) [5]. The average lesion size, such as depth of 3.08 ± 1.1 mm, range between 2 to 5.2 mm and area of 25.21 ± 20.66 mm 2 , range between 9 to 110 mm 2 , was close to other reports [3].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Identification of large Hill-Sachs lesions is important because it may indicate a predisposition for recurrent luxation. Our results, 91 % (71 out of 80 shoulders), are similar to other previous reports, such as 88 % (54 out of 61 shoulders) [3] and 94 % (81 out of 86 shoulders) [5]. The average lesion size, such as depth of 3.08 ± 1.1 mm, range between 2 to 5.2 mm and area of 25.21 ± 20.66 mm 2 , range between 9 to 110 mm 2 , was close to other reports [3].…”
Section: Discussionsupporting
confidence: 95%
“…Ultrasonography is a safe, cheap, available, comfortable and accurate method for diagnosis of Hill-Sachs lesions [3,5,9]. We present here our experience with ultrasound usage in the diagnosis of Hill-Sachs lesions.…”
mentioning
confidence: 97%
“…It's advantageous as it is readily available, avoids radiation, and allows one to obtain dynamic multi-planar images [38] . Ultrasound scanning has also been shown to have a sensitivity and specificity comparable with CT arthrograms in identifying Hill-Sachs lesions [39] . However, its limitations include operator dependence and it cannot be used to quantify the size of the humeral head defect, and thus has a limited role in pre-operative planning.…”
Section: Ultrasonography and Humeral Bone Lossmentioning
confidence: 99%
“…In concordance with fractures of the tuberosity complex of the humerus, it is reported that Hill-Sachs lesions are frequently missed with plain radiography [21], whereas sonographically Hill-Sachs lesions can be detected reliably (sensitivity: 91-96%, specificity: 95-100%, accuracy: 94-97%) [9,22]. Bodner et al [7] showed that common injuries like stress fractures, which are frequently overlooked on first radiographs, can be detected with US.…”
Section: Diagnostic Work-upmentioning
confidence: 92%
“…A limited number of articles has been published about the reliability and value of ultrasound (US) in the detection of fractures in general [2][3][4][5][6][7] and the proximal humerus [8][9][10][11][12] in particular.…”
Section: Introductionmentioning
confidence: 99%